Higher order aberrations and visual function in a young Asian population of high myopes. Issue 4 (April 2023) - Chay, Isaac W.; Lin, Sheng Tong; Lim, Edmund WL.; Heng, Wee Jin; Bin Ismail, Muhammad Amir; Tan, Marcus CL.; Zhao, Paul SB.; Nah, Gerard KM.; Ang, Bryan CH.
Abstract: Purpose: To examine the associations between higher order aberrations (HOAs), visual performance, demographics, and ocular characteristics in a young Asian population with high myopia. Methods: This was a retrospective review of military pre-enlistees conducted between March 2014 to September 2018. Visual acuity and contrast sensitivity were tested under photopic, mesopic and simulated night conditions. Ocular, corneal and internal HOAs were measured with a Hartmann–Shack wavefront aberrometer (KR-1W, Topcon Co., Tokyo, Japan). Results: 522 eyes of 263 consecutive subjects with severe high myopia (defined as spherical equivalent refraction [SER] ≤ −10.00D) in at least one eye, and high myopia (SER ≤ −6.00D) in the fellow eye, [mean (SD) SER −11.85 (2.03D)] were analysed. The mean (SD) age of subjects was 18.5 (1.6) years. Chinese eyes had significantly greater internal total HOA root-mean-square (RMS) compared to Malay eyes [mean difference (SD) 0.0246 (0.007) μm, p < 0.001). More negative SER was associated with greater ocular total HOA (p = 0.038), primary coma (p = 0.003) and tetrafoil (p = 0.025) RMS, as well as more positive ocular (p = 0.003) and internal primary spherical aberration (p = 0.009). Greater ocular total HOAs was associated with reduced visual acuity in simulated night conditions and low contrast, decreased contrast sensitivity under mesopic and simulated night conditions (all p < 0.05). Conclusions: Greater HOAs were associated with Chinese ethnicity and more negative SER in a young Asian population with high myopia. Greater HOAs were associated with poorer visual performance in low luminance and reduced contrast conditions.